2016
DOI: 10.1371/journal.pone.0162459
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Mycobacterium bovis from Cattle Reared in Midwest Brazil

Abstract: Mycobacterium bovis is the causative agent of bovine tuberculosis (BTB), the pathogen responsible for serious economic impact on the livestock sector. In order to obtain data on isolated M. bovis strains and assist in the control and eradication program for BTB, a cross sectional descriptive molecular epidemiology study in the Brazilian Midwest was conducted. Through spoligotyping and 24-loci MIRU-VNTR methods, 37 clinical isolates of M. bovis circulating in the region were analyzed, 10 isolated from the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
2
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 60 publications
5
34
2
7
Order By: Relevance
“…The spoligotype SB0121 is considered the most prevalent in several studies and the most frequent in Brazil (Zumárraga et al, ) and was observed in two (5.7%) buffaloes in the municipality of Autazes, as well as described in other studies, in the states of Bahia (Filho et al, ), Paraíba (Parreiras et al, ), Mato Grosso, Mato Grosso do Sul (Cazola et al, ), Goiás (Carvalho et al, ), Minas Gerais (Parreiras et al, ) and Rio Grande do Sul (Ramos et al, ). Outside of Brazil, SB0121 has been described in Colombia (Jojoa‐Jojoa et al, ), Argentina, Venezuela (Zumárraga et al, ), Mexico (Reyes et al, ), Portugal (Reis, ) and France (Hauer et al, ).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The spoligotype SB0121 is considered the most prevalent in several studies and the most frequent in Brazil (Zumárraga et al, ) and was observed in two (5.7%) buffaloes in the municipality of Autazes, as well as described in other studies, in the states of Bahia (Filho et al, ), Paraíba (Parreiras et al, ), Mato Grosso, Mato Grosso do Sul (Cazola et al, ), Goiás (Carvalho et al, ), Minas Gerais (Parreiras et al, ) and Rio Grande do Sul (Ramos et al, ). Outside of Brazil, SB0121 has been described in Colombia (Jojoa‐Jojoa et al, ), Argentina, Venezuela (Zumárraga et al, ), Mexico (Reyes et al, ), Portugal (Reis, ) and France (Hauer et al, ).…”
Section: Resultsmentioning
confidence: 56%
“…Other spoligotypes considered unusual were observed in this study, as SB1869, which had already been described in São Paulo by Rocha (Rocha, 2013), was identified in five buffaloes (14.3%) in (Table 1). Also considered unusual, SB1608 and SB1800 spoligotypes were isolated in this study, the spoligotype SB1608 isolated in buffalo in the municipality of Parintins had not previously been described in Brazil and was described in wild animals in Portugal (Carvalho et al, 2016), SB1800 was described in Brazil (www.mbovis.org) and identified in cattle in Apuí-AM (Table 1).…”
Section: Re Sults and Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…bovis são menos abundantes que para M. tuberculosis, no entanto a tipagem VNTR-MIRU foi usada em muitos países para estudos epidemiológicos de M. bovis (RORING et al, 2002;SKUCE et al, 2002;RORING et al, 2004;HILTY et al, 2005;ALLIX et al, 2006;JEON et al, 2008;ROMERO et al, 2008;BONIOTTI et al, 2009;Mc LERNON et al, 2010;SAHRAOUI et al, 2010;MANDAL et al, 2011;FIGUEIREDO et al, 2012;PARREIRAS et al, 2012;ROCHA et al, 2012;SUN et al, 2012;RAMOS et al, 2014;CARVALHO et al, 2016).…”
Section: Spoligotypingunclassified
“…Argentina (ZUMÁRRAGA et al, 2013;GHAVIDEL et al, 2018 Estudos anteriores no Brasil também relataram esse espoligotipo (ROCHA et al, 2013;CARVALHO et al, 2016). Esse perfil já foi detectado na Ásia, Europa e na Américas, sendo um dos espoligotipos mais disperso pelo mundo (ANDRIEVSKAIA et al, 2018;GHAVIDEL et al, 2018).…”
Section: Cálculo De Poder De Discriminação E Diversidade Alélicaunclassified